PENGUKURAN KINERJA INSTALASI FARMASI RUMAH SAKIT MITRA IDAMAN KOTA BANJAR DENGAN PENDEKATAN BALANCED SCORECARD - , Yopi Rikmasari; , Dr. Satibi M.Si., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Performance measurement using the Balanced Scorecard (BSC) need to be done considering strategy map that have been developed previously requires a measure of performance and need to know the measurement early performance. This research aim to know the performance pharmacy of Mitra Idaman Hospital using performance indicators in accordance with the strategic objectives have been composed in BSC strategy map. This research is descriptive study. Research subject is all pharmacy employees of Mitra Idaman Hospital, outpatient, doctor and nurse. Data acquired from primary data and secondary data. The analysis used with each performance indicator based on four BSC perspectives. Result of research on learning and growth perspective generally is less good, considered the 10 indicators measured only 3 indicators that show good results, which job satisfaction of employee are satisfied and not at the level of stress well as good organizational culture. Internal business process perspective generally show good results, from 8 performance indicators measured, dispensing time already meet the standards, the level of availability of the drug and formulary compliance nearly 100%. The percentage of dead stocks, percentage of pharmaceuticals expired and damage minimum. Realization conformity of purchase are close to the planning and Drug Use Review frequency perform still less. Customer perspective suggests that the results are less good because of the satisfaction of internal and external customers are not satisfied even though the level of patients visit shown the percentage of 94.12%. Financial perspective shows good results, ITOR 13.3, gross profit margin was 22.1%, revenue growth 22.15 % and the percentage of pharmacy departementâs revenue to hospital revenue 55,9 %.